Figurative Language Used in September Event 2018 - Apple and Apple Event - September 7 - Sihar Gilbert Marcelino Sitompul; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study investigates how Apple Inc. used metaphorical language in two of its product presentation videos.